2020
DOI: 10.1002/mats.202000054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Charge Regulation and Charge Heterogeneity on Complexation between Weak Polyelectrolytes and Weak Proteins Near Isoelectric Point

Abstract: enhanced bridging characteristics compared to completely dissociated polyelectrolytes. In contrast, for proteins exhibiting strong charge heterogeneities, dissociable polyelectrolytes are seen to exhibit weaker bridging compared to completely dissociated polyelectrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Mixtures of proteins with synthetic polyelectrolytes have numerous applications in food technology, biotechnology, and medicine. The properties of protein–polyelectrolyte complexes in aqueous solutions depend on the component structure, their concentrations, solution pH, and ionic strength. The formation of primary complexes can lead to a coacervate formation and phase separation in the system. Polyelectrolyte–protein complexes are formed as a result of strong electrostatic interactions between oppositely charged macromolecules, hydrogen bonding, and hydrophobic interactions. , Extensive studies of Dubin and co-workers showed that electrostatic interactions are one of the most important factors determining the properties of protein–polyelectrolyte aqueous systems. ,, At the same time, it was shown that even when a protein and a polyelectrolyte were similarly charged, the formation of complexes can still be possible due to the charge heterogeneity of the surface of protein globules and hydrophobic interactions between the components. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of proteins with synthetic polyelectrolytes have numerous applications in food technology, biotechnology, and medicine. The properties of protein–polyelectrolyte complexes in aqueous solutions depend on the component structure, their concentrations, solution pH, and ionic strength. The formation of primary complexes can lead to a coacervate formation and phase separation in the system. Polyelectrolyte–protein complexes are formed as a result of strong electrostatic interactions between oppositely charged macromolecules, hydrogen bonding, and hydrophobic interactions. , Extensive studies of Dubin and co-workers showed that electrostatic interactions are one of the most important factors determining the properties of protein–polyelectrolyte aqueous systems. ,, At the same time, it was shown that even when a protein and a polyelectrolyte were similarly charged, the formation of complexes can still be possible due to the charge heterogeneity of the surface of protein globules and hydrophobic interactions between the components. ,,,, …”
Section: Introductionmentioning
confidence: 99%